2014
DOI: 10.3892/ijo.2014.2430
|View full text |Cite
|
Sign up to set email alerts
|

Klotho suppresses growth and invasion of colon cancer cells through inhibition of IGF1R-mediated PI3K/AKT pathway

Abstract: Klotho (KL) was originally characterized as an aging suppressor gene, and has been identified as a tumor suppressor gene in a variety of cancers including colon cancer. However, the potential role and molecular events for KL in colon cancer remain unclear. The present study aimed to investigate the expression of KL in human colon cancer by immunohistochemistry, and to analyze the correlation between KL expression and clinicopathological characteristics of patients with colon cancer. Functional analysis after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 30 publications
3
51
0
5
Order By: Relevance
“…It functions through enhancing the protein synthesis required for cell proliferation [17]. Nowadays, with more and more researches about IGF1R, many other regulatory factors has been presented, such as let-7d-5p, miR-493, miR-497 and tumor suppressor p53, klotho [18][19][20][21][22]. Inflammation is known as a hallmark of cancer wherein diverse immune cells exert either pro-or anti-tumor properties and affect therapeutic resistance [23].…”
Section: Introductionmentioning
confidence: 99%
“…It functions through enhancing the protein synthesis required for cell proliferation [17]. Nowadays, with more and more researches about IGF1R, many other regulatory factors has been presented, such as let-7d-5p, miR-493, miR-497 and tumor suppressor p53, klotho [18][19][20][21][22]. Inflammation is known as a hallmark of cancer wherein diverse immune cells exert either pro-or anti-tumor properties and affect therapeutic resistance [23].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of this pathway in the development of colon cancer and metastasis, including cell proliferation, apoptosis and migration, has been extensively investigated (15)(16)(17)(18). Furthermore, the blockade of PI3K/Akt activity in colon cancer cells has shown promising anti-cancer effects (19)(20)(21)(22). Recent studies have demonstrated that the downstream factor of the PI3K/Akt pathway, the mammalian target of rapamycin (mTOR), is a potential therapeutic target in various types of cancer, including non-small cell lung cancer (23) (26), non-Hodgkin's lymphoma (27) and leukemia (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data indicate klotho as a potent tumour suppressor in a wide array of malignancies, including breast, lung and pancreatic cancers 13 15–18. Mechanisms mediating the tumour suppressor activities of klotho include modulation of bFGF signalling,13 18 inhibition of the insulin/IGF-1 pathways 13 15 18 19 and inhibition of the Wnt/β-catenin pathway 20 21…”
Section: Introductionmentioning
confidence: 99%